The Water Quality Survey of Mae Chan Basin at Chiang Rai Province - Kitchainukul, Waraporn; Thongsri, Tepwitoon; Thipvisaid, Natawan; Tirapitayanon, Wasan; Muangkaew, Kanya; Srisane, Jirachatr; Thonganan, Veerapat (Bulletin of Applied Sciences, 2022)
Mae-Chan Basin is one of the important water resources in Chiang-Rai Province. It was used as raw water to produce tap water and to be fish conservative area; therefore, it is necessary to study Mae-Chan water quality. The area of this study was divided into 3 parts. First part is the beginning of Mae-Chan Basin. Next, is the middle part and the last part is the end of Mae-Chan Basin. The aim of the study is to focus on changing of water quality of Mae-Chan Basin. The results showed that Mae-Chan Basin was Nitrogen polluted because all study area found Nitrate concentration between 9 and 12 mg/L while the standard limit is 5 mg/L. However, other parameters showed that water quality type 2 at the beginning part of Mae-Chan Basin was classified. The middle part of study area, where it passed through communities, BOD and Total Coliform Bacteria were increased and type 5 was classified. Decreasing of BOD and Total Coliform Bacteria was found at the end of Mae-Chan Basin, thus type 4 was classified.